2018
DOI: 10.2147/clep.s158110
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen administration and the risk of acute kidney injury: a self-controlled case series study

Abstract: BackgroundAcetaminophen (APAP) is frequently used for analgesia and is considered safer than nonsteroidal anti-inflammatory drugs (NSAIDs) for the kidneys. However, there is little epidemiological evidence of the association between APAP and acute kidney injury (AKI).ObjectivesTo examine the association between APAP and AKI using the self-controlled case series (SCCS) method, which is a novel strategy to control between-person confounders by comparing the risk and reference periods in each patient.MethodsWe pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…In a cohort study in subjects with normal renal function, the relative risk of renal failure was significantly lower in APAP group than NSAIDs. 23) Hiragi et al 24) first reported epidemiological evidence for an association between APAP administration and AKI development using self-controlled case series method. They concluded that the results presumably support the general clinicians' impression that APAP is safer for the kidney than NSAIDs.…”
Section: Risk For Acute Kidney Injury and Gas-trointestinal By Apap: mentioning
confidence: 99%
“…In a cohort study in subjects with normal renal function, the relative risk of renal failure was significantly lower in APAP group than NSAIDs. 23) Hiragi et al 24) first reported epidemiological evidence for an association between APAP administration and AKI development using self-controlled case series method. They concluded that the results presumably support the general clinicians' impression that APAP is safer for the kidney than NSAIDs.…”
Section: Risk For Acute Kidney Injury and Gas-trointestinal By Apap: mentioning
confidence: 99%
“…APAP/paracetamol-induced nephrotoxicity is amongst the least causatives of renal injury (Hiragi et al, 2018). The overdose of paracetamol is associated with elevated serum levels of creatinine and urea, oxidative stress (Canayakin et al, 2016), apoptosis, and DNA damage (Lorz et al, 2004).…”
Section: Drug-induced Nephrotoxicitymentioning
confidence: 99%
“…The enzymatic production of H 2 S involves two systems, including pyridoxal 5′-phosphate-dependent (CBS and CSE) and pyridoxal 5′-phosphate-independent (3-MPST) systems ( Stipanuk and Beck, 1982 ; Mikami et al, 2011 ). CBS mediates the conversion of Hcy and serine to produce cystathionine, which is then converted by CSE into Cys, α-ketobutyrate, and ammonia ( Stipanuk and Ueki, 2011 ). CBS facilitates β replacement of thiol (-SH) group of the Cys with Hcy to produce H 2 S; meanwhile, CSE facilitates α, β, and γ elimination of cystathionine, Hcy, and Cys to form H 2 S ( Chiku et al, 2009 ).…”
Section: The Biosynthesis Of Hydrogen Sulfidementioning
confidence: 99%
“…Недавно были представлены данные крупного популяционного исследования S. Hiragi и соавт. [35], в котором изучалась связь между использованием ПАР и развитием 5650 случаев острой почечной недостаточности (ОПН). Отношение инцидентов ОПН для ПАР составило 1,03 (95% ДИ 0,95-1,12), что указывает на отсутствие риска при использовании данного препарата.…”
Section: парацетамолunclassified